2020
DOI: 10.1007/s10948-020-05518-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Investigation of Bi2S3@Fe3O4 Nanocomposites for Medical Applications

Abstract: Bi 2 S 3 and Fe 3 O 4 nanostructures as well as Bi 2 S 3 @Fe 3 O 4 nanocomposites were produced using hydrothermal synthesis. Scanning electron microscopy (SEM), energy dispersive spectra (EDS) and X-ray diffraction (XRD) were used in the characterization of the nanocomposites. The effect of heat treatment on chemical, physical and magnetic properties of the nanostructures was investigated in this study. It was determined that the duration of heat treatment affects the size and shape of the nanostructures. Bi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…In their magnetic saturation measurements of Fe3O4@Bi2S3 nanoflowers synthesized by the hydrothermal method, Yetim et al, found a value of 89.8 emu/g for the Fe3O4 nanostructure [17]. In a similar study, Karacam et al reported the magnetic saturation values of the Fe3O4 nanostructures as 87.7 emu/g and 90.7 emu/g [18]. The magnetic value of the ZnO additive obtained in this study decreased considerably.…”
Section: Optical Properties Of Zno@fe3o4 Nanostructuressupporting
confidence: 58%
See 1 more Smart Citation
“…In their magnetic saturation measurements of Fe3O4@Bi2S3 nanoflowers synthesized by the hydrothermal method, Yetim et al, found a value of 89.8 emu/g for the Fe3O4 nanostructure [17]. In a similar study, Karacam et al reported the magnetic saturation values of the Fe3O4 nanostructures as 87.7 emu/g and 90.7 emu/g [18]. The magnetic value of the ZnO additive obtained in this study decreased considerably.…”
Section: Optical Properties Of Zno@fe3o4 Nanostructuressupporting
confidence: 58%
“…The precipitate was kept at 80 ⁰C for 12 hours (ZnO@Fe3O4-1:1). The same procedures were repeated for 0.656 g of Fe3O4.7H2O and 3.2 g of NaOH (ZnO@Fe3O4-1:2) [17][18][19]. Also, such process are illustrated schematically in Fig.…”
Section: Synthesis Of Magnetic Zno@fe3o4 Composite Nanostructuresmentioning
confidence: 99%
“…Hydrothermal method is a highly efficient production process with minimum production cost which enables researchers to control nanostructure morphology. The method also provide good nanostructure size and shape control [19].…”
Section: Introductionmentioning
confidence: 99%
“…These core shell nanocomposite may act as a promising material photo thermal therapy and magnetic hyperthermia application. [12].N.K yeitim et alhave shown the structural and catalytic properties of Fe3O4 doped Bi2S3 nanocomposite using hydrothermal method and they have observed that these nanocomposite have the potential to be used in the waste water treatment [13].Furthermore, the fabrication of these core shell nanomaterial's are usually a complicated process ,that takes a lot of time and occurs at an elevated temperature. Although lot of work has been researched related to this core shell material but very less work has been reported in the magneto optical fiber sensing application of the core shell material.…”
Section: Introductionmentioning
confidence: 99%